Optimization of peptide nucleic acid antisense oligonucleotides for local and systemic dystrophin splice correction in the mdx mouse. - Yin, H; Betts, C; Saleh, A; Ivanova, G; Lee, H; Seow, Y; Kim, D; Gait, M; Wood, M (2010)
Antisense oligonucleotides (AOs) have the capacity to alter the processing of pre-mRNA transcripts in order to correct the function of aberrant disease-related genes. Duchenne muscular dystrophy (DMD) is a fatal X-linked muscle degenerative disease that arises from mutations in the DMD gene leading to an absence of dystrophin protein. AOs have been shown to restore the expression of functional dystrophin via splice correction by intramuscular and systemic delivery in animal models of DMD and in DMD patients via intramuscular administration. Major challenges in developing this splice correction therapy are to optimize AO chemistry and to develop more effective systemic AO delivery. Peptide nucleic acid (PNA) AOs are an alternative AO chemistry with favorable in vivo biochemical properties and splice correcting abilities. Here, we show long-term splice correction of the DMD gene in mdx mice following intramuscular PNA delivery and effective splice correction in aged mdx mice. Further, we report detailed optimization of systemic PNA delivery dose regimens and PNA AO lengths to yield splice correction, with 25-mer PNA AOs providing the greatest splice correcting efficacy, restoring dystrophin protein in multiple peripheral muscle groups. PNA AOs therefore provide an attractive candidate AO chemistry for DMD exon skipping therapy.